'In my end is my beginning': Lumen gentium and the Priority of Doxology. (May 2014) - Ruddy, Christopher
Essential to the full reception of Lumen gentium is a recovery of that document's doxological ecclesiology, which presents the Church—even on earth—as most fully itself when it praises God. This article proposes that acknowledging the priority of doxology in the life of the Church will foster a more effective evangelization, service, and mission. It first surveys Lumen gentium 's context, achievements, seeds, and incomplete reception. It then argues for the centrality of holiness and doxology in ecclesiology, looking at both several theologians (Frans Jozef van Beeck, Khaled Anatolios, Joseph Ratzinger) and exemplary passages from Lumen gentium . The article concludes with a brief reflection on the importance of Lumen gentium 's doxological ecclesiology for addressing contemporary challenges.